A double-layer moisture barrier & antireflective film based on bridged polysilsesquioxane and porous silica. Issue 70 (31st July 2015) - Zhang, Cong; Zhang, Ce; Sun, Jinghua; Ding, Ruimin; Zhang, Qinghua; Xu, Yao
<x xml:space="preserve">Abstract</x> Preparation process of a double-layer moisture barrier protective & antireflective film.